Fried green tomatoes [videorecording (DVD)] - Avnet, Jon, 1949-; Bates, Kathy, 1948-; Tandy, Jessica; Masterson, Mary Stuart, 1966-; Parker, Mary-Louise; Flagg, Fannie (Universal Home Video, 1998)
A chance encounter in a nursing home leads to an unexpected friendship between a dowdy housewife and a spry octagenarian who tells her the story of a fiercely independent woman half a century ago, inspiring the housewife to change her life, often with hilarious results.